2021
DOI: 10.1007/s12325-021-01825-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Healthcare Resource Utilization (HRU) and Costs of Patients with Paroxysmal Nocturnal Hemoglobinuria (PNH) Receiving Eculizumab in a US Population

Abstract: Introduction: To evaluate the economic burden and treatment patterns of patients with paroxysmal nocturnal hemoglobinuria (PNH) treated with eculizumab, a C5 inhibitor, who were defined as blood transfusion-dependent (TD) versus blood transfusion-free (TF) in the US population. Methods: Patients aged at least 12 years with at least two claims for eculizumab infusion (first claim was the index date) were identified from the IBM Ò MarketScan Ò Research Databases (April 1, 2014-September 30, 2019. The overall PNH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 26 publications
7
25
3
Order By: Relevance
“…The reported ranges for FACIT‐Fatigue and EORTC QLQ‐C30 scores were worse (greater impairment) than those of the general population, and nearly all patients reported impaired work productivity and activity. As trends were generally similar across all four subgroups, these data generally align with and expand upon previous studies suggesting persistent unmet need associated with C5i therapy 2,5,6,16,22,24,28 …”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The reported ranges for FACIT‐Fatigue and EORTC QLQ‐C30 scores were worse (greater impairment) than those of the general population, and nearly all patients reported impaired work productivity and activity. As trends were generally similar across all four subgroups, these data generally align with and expand upon previous studies suggesting persistent unmet need associated with C5i therapy 2,5,6,16,22,24,28 …”
Section: Discussionsupporting
confidence: 86%
“…To our knowledge, this is the first cross-sectional, multinational study of European patient-reported clinical and humanistic outcomes among As trends were generally similar across all four subgroups, these data generally align with and expand upon previous studies suggesting persistent unmet need associated with C5i therapy. 2,5,6,16,22,24,28 Overall, patient characteristics were generally consistent with baseline findings for the International PNH Registry population (at 2011 and 2017), as well as populations from retrospective observational studies and a counterpart survey study conducted in the United States. 2,5,6,28,37 Specifically, our observed overall Hb levels align with the most recent international registry data (median 10.0 vs. 9.8 g/dL) 2 ; median Hb levels for the eculizumab subgroup were also generally consistent with a real-world study of UK patients treated for at least 13 months (10.0 vs. 10.9 g/dL).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Further evidence regarding the HRU (eg, hospitalizations, outpatient visits) and direct medical costs among eculizumab-treated PNH patients is also warranted. 28 In particular, there is a need for comparative assessments of the economic and clinical outcomes among eculizumab-treated patients who received a regularly scheduled dose relative to those with deviations from label-recommended dosing, including those who required dose escalation.…”
Section: Discussionmentioning
confidence: 99%